Asymmetry in Israeli academia: Attitudes of Bedouin female students about their relationship with Jewish female students - Abu-Gweder, Aref (Journal of International Students, 2025)
This study explores the attitudes of Bedouin female students towards their Jewish peers in multicultural courses at teaching colleges in Israel. Based on a sample of 30 participants, findings reveal mixed emotions. While Bedouin students value cultural diversity and opportunities for cross-cultural engagement, they face challenges stemming from the broader social dynamics in the country. Multicultural groups aim to foster dialogue and shared perspectives, but Jewish students often maintain a dominant position, avoiding deeper engagement with intergroup relations. In contrast, Bedouin students emphasize their minority identity, which is shaped by religious, social, and cultural factors, framing themselves in relation to their socio-national background. Despite these challenges, both groups collaborate and support one another in achieving academic success, demonstrating the potential of multicultural settings to promote cooperation amidst diversity.